Overvaluation and the Choice of Alternative Earnings Management Mechanisms - Badertscher, Brad A. (The Accounting Review, 2011)
ABSTRACT In this study I examine how the degree and duration of overvaluation affect management's use of alternative within-GAAP earnings management, restrictions on further exploitation of within-GAAP accruals management, and subsequent non-GAAP earnings management. Further, I examine how one type of earnings management segues into another type as overvaluation persists. I present evidence that the longer the firm is overvalued, the greater is the amount of total earnings management. I also find that managers engage in accruals management in the early stages of overvaluation before moving to real transactions management, in order to sustain their overvalued equity. Finally, I find that the longer a firm is overvalued, the more likely it is to engage in one of the most egregious forms of earnings management, non-GAAP earnings management. Collectively, the results suggest that the duration of firm overvaluation is an important determinant of managements' choice of alternative earnings management mechanisms. JEL Classifications: M41, M43, M44. Data Availability: Data are available from sources identified in the text.